2009
DOI: 10.1080/09593980902776654
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maitland mobilization and exercises for the treatment of shoulder adhesive capsulitis: A single-case design

Abstract: The purpose of this single-case design (ABCBC) was to investigate the response of shoulder motions, pain, and function to two commonly used physiotherapy management approaches. An individual with stage three shoulder adhesive capsulitis was treated with exercise (phase B) and exercise plus mobilization (phase C). Initially, a "baseline" phase (phase A) when treatment had not started was established for comparison. Two types of Maitland "accessory" glenohumeral mobilization techniques, anteroposterior mobilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 35 publications
1
25
0
1
Order By: Relevance
“…Thus, these results allowed rejection of the null hypothesis and thereby supported to accept the experimental hypothesis. These results strongly support the earlier findings of study [16] that investigated the shoulder motion pain and function by using mobilization and exercises on single case design and concluded that all four movements improved, although more gain in motion was observed when mobilizations were added.…”
Section: Abduction Rangessupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, these results allowed rejection of the null hypothesis and thereby supported to accept the experimental hypothesis. These results strongly support the earlier findings of study [16] that investigated the shoulder motion pain and function by using mobilization and exercises on single case design and concluded that all four movements improved, although more gain in motion was observed when mobilizations were added.…”
Section: Abduction Rangessupporting
confidence: 90%
“…Intervention consisted of the Codman exercise [4], shoulder wheel exercises [6], self-stretching exercises [6], wall-ladder exercises [6,16], and self-stretching exercises (for improving abduction, flexion, external rotation, internal rotation, and horizontal adduction).…”
Section: Common Supervised Exercisesmentioning
confidence: 99%
“…28,49,50 Jewell et al 20 concluded in a retrospective cohort study that the use of joint mobilization and exercise was associated with improved outcomes, whereas poor outcomes were associated with providing massage, ultrasound, phonophoresis, and iontophoresis as the primary interventions. Stretching exercises are advocated for patients with adhesive capsulitis.…”
Section: T T Discussion: This Case Report Describesmentioning
confidence: 99%
“…[2][3][4][5] Joint mobilization techniques are thought to produce various therapeutic effects. 6 A biomechanical effect may exist when forces are directed towards capsular resistance.…”
Section: Introductionmentioning
confidence: 99%
“…9 Furthermore, mobilization techniques may serve to improve or maintain joint mobility by improving the flow and exchange of synovial fluid. [7][8][9] Consequently, gliding of the GH joint is used in the treatment of a variety of pathologies, such as impingement, 4 adhesive capsulitis 3,5,10 and in post-operative rehabilitation. 1 The glenohumeral posterior glide and distraction mobilizations have been well researched in regard to their ability to produce tissue deformation and stretch of the glenohumeral joint capsule.…”
Section: Introductionmentioning
confidence: 99%